Handbook of organic conductive molecules and polymers conductive polymers : syntilesis and electrical properties - Nalwa, Hari Singh (John Wiley & Sons, 1997)
Conductive polymers----polymers that conduct electricity----have applications in telecommunications, electronics, materials science, chemistry and physics. The four self--contained volumes of this handbook thoroughly explore all aspects of conductive polymers including chemical and physical properties, technology and applications.